PERIBAHASA DALAM BAHASA MELAYU DIALEK TAYAN HILIR - Herningsih, Okta; Patriantoro, Patriantoro; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractMalay language in Tayan Hilir dialect grows and thrives in Tayan Hilir District, Sanggau Regency. The researcher interested in this title because proverbs can improve and clear up a sentence. The purpose of this research is to describe type, meaning, and function of the proverbs. The methods used are referring, proficient, and descriptive in the form of qualitative research. The data source is from the native speakers of Malay language in Tayan Hilir dialect. The techniques used in collecting the data are observation, referring-engaged-competent, record, and note. Based on the data analysis, the result of this research shows that, in Malay language in Tayan Hilir dilect, there are 141 proverbs, and divided into 6 types, they are 62 sayings, 12 parables, 58 phrase (idiom), 5 bywords, 2 imageries, 2 allusions. The meaning of proverb in Malay language in Tayan Hilir dialect is the meaning that still can be traced and tracked from the meaning of its elements because of the association between the original meaning and its meaning as a proverb. There are 4 functions of proverb in Malay language in Tayan Hilir dialect, those are, advice, insinuation (subtle scolding), compliment, and diplomatic language (affirmation).  Keywords: Proverb, Malay Dialect of Tayan Hilir